Synthesis and characterisation of CdO nanoparticles: An efficient nanomaterial for the removal of Rhodamine B. (2022) - Geetha Malini, P.S.; Durgadevi, P.; Senthil Kumar, N.; Rani, S.
Abstract: An Environmentally friendly method is reported for the synthesis of nanoscale CadmiumOxide using plant extract as a reducing agent. Cadmium oxide was synthesised by a simple solution combustion method using Cadmium Chloride monohydrate and Phyllantus Emblica extract and calcined at elevated temperatures. Biosynthesised CadmiumOxide Nanoparticles (CdONPs) was calcinated at different temperatures like 70, 200, 400 and 600 °C. CdONPs calcined at higher temperature was appraised for the removal of Rhodamine B (RhB) from aqueous solution. The developed adsorbent was characterized by TGA, DTA, FTIR, XRD, FESEM, EDAX and TEM. XRD revealed that Cd(OH)2 nanoparticles with hexagonal structure transform into CdONPs with cubic structure. The adsorption ability of the CdONPs was systematically investigated using batch experiments. The factors investigated include initial concentration, adsorbent dosage, contact time and pH. The CdONPs, calcined at 600 °C exhibit good nanomaterial for the removal of RhB (93% degradation of RhB for 0.1 g dosage within 80 min). Adsorption follows Langmuir isotherm and ΔG° = −79.55 KJ/mol indicates that the adsorption is chemisorption and spontaneous. The kinetic data for the adsorption process obeyed a pseudo-second-order kinetic model with R 2 of 0.99. Present work has proved that CdONP is a novel low-cost nanomaterial and plays an important role in environmental protection.